2012
DOI: 10.1039/c2sm26179k
|View full text |Cite
|
Sign up to set email alerts
|

Electrorheological fluids: smart soft matter and characteristics

Abstract: An electrorheological fluid, a special type of suspension with controllable fluidity by an electric field, generally contains semiconducting or polarizable materials as electro-responsive parts. These materials align in the direction of the applied electric field to generate a solid-like phase in the suspension. These electro-responsive smart materials, including dielectric inorganics, semiconducting polymers and their hybrids, and polymer/inorganic composites, are reviewed in terms of their mechanism, rheolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
159
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(163 citation statements)
references
References 209 publications
(250 reference statements)
3
159
0
1
Order By: Relevance
“…These novel properties have made ER fluids the most important intelligent/smart materials for they can be served as the electric-mechanical interface to fulfill the conversion of electric to force. Thus, ER fluids have been shown to have various potential applications in medical, aerospace, automotive, microfluidics, and many other industries [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These novel properties have made ER fluids the most important intelligent/smart materials for they can be served as the electric-mechanical interface to fulfill the conversion of electric to force. Thus, ER fluids have been shown to have various potential applications in medical, aerospace, automotive, microfluidics, and many other industries [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Among various conjugated polymers ER materials, PANI has attracted significant attentions due to simple preparation, conductivity adjustable by simply doped and dedoped process, and good thermal and environmental stability [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Since organic-inorganic core/shell nanoparticles (NPs) often exhibit improved physical and chemical properties over the single organic or inorganic component, and can be utilized in broad areas of coatings, electronics, catalysis and diagnostics, the fabrication of organic-inorganic composite particles with core-shell structure has attracted high attentions of many researchers over the past decades in both fundamental researches [9][10][11][12][13][14][15] and industrial applications. [16][17][18] Calcium carbonate (CaCO 3 ) powder has been widely used as fillers in plastic, rubber, adhesive and coating industries to improve the mechanical properties and decrease the product cost. [19][20][21] The simplest way to prepare this composite is to blend polymer with CaCO 3 , but the reinforcing phenomena are barely seen, which is mostly attributed to poor compatibility and interaction between CaCO 3 filler and matrix polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have shown that the ER response decreases with the increasing frequency of the electric field beyond a frequency of 100 Hz [3]. Other workers have studied the effects of additives such as water, urea, or other polar molecules [4][5][6][7][8][9] on performance of an ER fluid. These studies have shown that these additives improve the ER response of ER fluids in terms of shear stress or elastic modulus.…”
Section: Introductionmentioning
confidence: 99%